Fundamental Analysis and Trading Volume on Stock Prices with Company Size as a Control Variable - Yanuar Indra Kurniawan; Hadi Pramono; Iwan Fakhruddin; Rina Mudjiyanti (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine the influence of fundamental variables and trading volume on stock prices in energy sector companies. This research uses the variables Debt Equity Ratio, Return on Assets, Trading Volume and Share Price. The population used in this research is energy sector companies in 2019 - 2022. The sampling method in this research is purposive sampling method so that 120 company data is obtained in 4 years. The analysis method uses multiple linear regression. Conclusions from the results of this research in the energy sector on the Indonesia Stock Exchange (BEI) in the 2019-2022 period the debt equity ratio variable has a negative and significant influence on shares, the return on assets variable has a negative and significant influence on share prices, the trading volume variable does not has an influence on share prices. Then the control variable, namely company size, has no effect on share prices.